TECHNICAL EFFICIENCY IN TRANSPORT MANUFACTURING FIRMS: EVIDENCE FROM MALAYSIA - Mohd Fahmy-Abdullah; Rahmah Ismail; Noorasiah Sulaiman; Basri Abdul Talib (Asian Academy of Management Journal, 2017)
This study aims to identify the level of technical efficiency and the determinants of technical inefficiency for transport manufacturing firms in Malaysia for 2010 using cross-sectional data of 130 firms acquired from the Department of Statistics (DOS). Based on the stochastic frontier analysis (SFA) approach, the results of the study reveal that the average level of technical efficiency is moderate. The estimated result identifies the important determinants of technical inefficiency which are due to employee wage rates as well as the cost of information and communication technology. The fundamental implications of this study are that transport manufacturing firms need to boost motivation among employees and strengthen the network of the production market via wage increment and communication cost.